The electrochemical behaviour of ferrocene in deep eutectic solvents based on quaternary ammonium and phosphonium salts - Bahadori, L.; Manan, N.S.; Chakrabarti, M.H.; Hashim, M.A.; Mjalli, F.S.; AlNashef, I.M.; Hussain, Mohd Azlan; Low, C.T. (Royal Society of Chemistry, 2013)
The electrochemical behaviour of ferrocene (Fc) is investigated in six different deep eutectic solvents (DESs) formed by means of hydrogen bonding between selected ammonium and phosphonium salts with glycerol and ethylene glycol. Combinations of cyclic voltammetry and chronoamperometry are employed to characterise the DESs. The reductive and oxidative potential limits are reported versus the Fc/Fc+ couple. The diffusion coefficient, D, of ferrocene in all studied DESs is found to lie between 8.49 × 10 -10 and 4.22 × 10-8 cm2 s-1 (these do not change significantly with concentration). The standard rate constant for heterogeneous electron transfer across the electrode/DES interface is determined to be between 1.68 × 10-4 and 5.44 × 10-4 cm s-1 using cyclic voltammetry. These results are of the same order of magnitude as those reported for other ionic liquids in the literature.